2013
DOI: 10.1016/j.bpj.2013.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Evidence for β-Hairpin Structure within MAX8 Designer Peptide Nanofibers

Abstract: MAX8, a designer peptide known to undergo self-assembly following changes in temperature, pH, and ionic strength, has demonstrated usefulness for tissue engineering and drug delivery. It is hypothesized that the self-assembled MAX8 nanofiber structure consists of closed β-hairpins aligned into antiparallel β-sheets. Here, we report evidence from solid-state NMR spectroscopy that supports the presence of the hypothesized β-hairpin conformation within the nanofiber structure. Specifically, our (13)C-(13)C two-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
4
19
0
Order By: Relevance
“…Amyloid fibrils formed in vitro are generally polymorphic unless special fibril growth protocols are used, such as repeated seeding (8) or long periods of incubation with agitation to promote convergence to a single structure with lowest free energy (35). Prior solid-state NMR studies of the gel-forming peptides RADA16-I and MAX8 suggested polymorphism or incomplete molecular structural order within the hydrogels (14,20).…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid fibrils formed in vitro are generally polymorphic unless special fibril growth protocols are used, such as repeated seeding (8) or long periods of incubation with agitation to promote convergence to a single structure with lowest free energy (35). Prior solid-state NMR studies of the gel-forming peptides RADA16-I and MAX8 suggested polymorphism or incomplete molecular structural order within the hydrogels (14,20).…”
Section: Discussionmentioning
confidence: 99%
“…As with their naturally occurring counterparts, structural studies of these designer amyloids benefit from valuable insights enabled by ssNMR [23, 114118]. In most cases, these amyloid- or cross-β-based materials are based on short amyloidogenic peptides that may be modified with acyl chains or by cross-linking [23, 115, 116].…”
Section: Designer Amyloidsmentioning
confidence: 99%
“…This includes the parallel β-sheet solenoids as illustrated in Fig. 2, as well as antiparallel architectures with and without β-hairpins[20, 42, 100, 118]. …”
Section: Recurring Themesmentioning
confidence: 99%
“…Nuclei with a spin quantum number of I = ½ such as 1 H, 13 C, 19 F, 29 Si, 15 N, and 31 P yield highresolution NMR spectra and are therefore particularly informative in the study of polymer systems. These nuclei display spectra with unique peaks for each magnetically inequivalent nuclei in the chemical structure, essentially enabling the study of individual atomic positions within the chemical structure of a polymer [3].…”
Section: Nmr Spectroscopy Of Solid Polymersmentioning
confidence: 99%
“…MAX8 is an amphiphilic peptide composed of 20 amino acids, having the amino acid sequence VKVKVKVKVDPPTKVEVKVKVNH2, where K and E are hydrophilic residues and V hydrophobic residues [15]. The self-assembled peptide contains a β-strand hairpin structure aligned into antiparallel β-sheets.…”
Section: Protein Systemsmentioning
confidence: 99%